Do relevant shear forces appear in isokinetic shoulder testing to be implemented in biomechanical models?. (27th April 2018) - Bélaise, Colombe; Michaud, Benjamin; Boucher, Mathieu; Begon, Mickaël
Abstract: Isokinetic dynamometers measure joint torques about a single fixed rotational axis. Previous studies yet suggested that muscles produce both tangential and radial forces during a movement, so that the contact forces exerted to perform this movement are multidirectional. Then, isokinetic dynamometers might neglect the torque components about the two other Euclidean space axes. Our objective was to experimentally quantify the shear forces impact on the overall shoulder torque, by comparing the dynamometer torque to the torque computed from the contact forces at the hand and elbow. Ten healthy women performed isokinetic maximal internal/external concentric/eccentric shoulder rotation movements. The hand and elbow contact forces were measured using two six-axis force sensors. The main finding is that the contact forces at the hand were not purely tangential to the direction of the movement (effectiveness indexes from 0.26 ± 0.25 to 0.54 ± 0.20), such that the resulting shoulder torque computed from the two force sensors was three-dimensional. Therefore, the flexion and abduction components of the shoulder torque measured by the isokinetic dynamometer were significantly underestimated (up to 94.9%). These findings suggest that musculoskeletal models parameters should not be estimated without accounting for the torques about the three space axes.